Verso il dramaturg: rilevarsi nell’officina di Simona Gonella - Malinarić, Jovana (Italogramma, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.01047);" role="presentation">L’articolo <span dir="ltr" style="left: calc(var(--scale-factor)*124.34px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901427);" role="presentation">tratta <span dir="ltr" style="left: calc(var(--scale-factor)*153.38px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.25393);" role="presentation">il <span dir="ltr" style="left: calc(var(--scale-factor)*164.54px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.934983);" role="presentation">divenire <span dir="ltr" style="left: calc(var(--scale-factor)*208.25px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.919763);" role="presentation">della <span dir="ltr" style="left: calc(var(--scale-factor)*235.97px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.953282);" role="presentation">figura <span dir="ltr" style="left: calc(var(--scale-factor)*268.97px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.931381);" role="presentation">polivalente e <span dir="ltr" style="left: calc(var(--scale-factor)*336.55px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.911361);" role="presentation">sofisticata <span dir="ltr" style="left: calc(var(--scale-factor)*389.59px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91293);" role="presentation">del <span dir="ltr" style="left: calc(var(--scale-factor)*408.67px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901975);" role="presentation">dramaturg <span dir="ltr" style="left: calc(var(--scale-factor)*462.46px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.97243);" role="presentation">all’interno <span dir="ltr" style="left: calc(var(--scale-factor)*516.82px); top: calc(var(--scale-factor)*301.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.919763);" role="presentation">della <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.871978);" role="presentation">prassi <span dir="ltr" style="left: calc(var(--scale-factor)*103.34px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.87938);" role="presentation">teatrale <span dir="ltr" style="left: calc(var(--scale-factor)*141.86px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925175);" role="presentation">italiana. <span dir="ltr" style="left: calc(var(--scale-factor)*183.62px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.984);" role="presentation">In <span dir="ltr" style="left: calc(var(--scale-factor)*196.97px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.911879);" role="presentation">particolare, <span dir="ltr" style="left: calc(var(--scale-factor)*254.45px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.882636);" role="presentation">prendendo <span dir="ltr" style="left: calc(var(--scale-factor)*308.45px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00214);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*321.17px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.830436);" role="presentation">esame <span dir="ltr" style="left: calc(var(--scale-factor)*354.43px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.932492);" role="presentation">l’esempio <span dir="ltr" style="left: calc(var(--scale-factor)*405.07px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999572);" role="presentation">di <span dir="ltr" style="left: calc(var(--scale-factor)*417.79px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">Simona <span dir="ltr" style="left: calc(var(--scale-factor)*457.75px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915577);" role="presentation">Gonella, <span dir="ltr" style="left: calc(var(--scale-factor)*502.06px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.860123);" role="presentation">cerca <span dir="ltr" style="left: calc(var(--scale-factor)*530.62px); top: calc(var(--scale-factor)*315.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999572);" role="presentation">di <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.888817);" role="presentation">delineare i <span dir="ltr" style="left: calc(var(--scale-factor)*124.94px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.970596);" role="presentation">tratti p<span dir="ltr" style="left: calc(var(--scale-factor)*156.50px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.943714);" role="presentation">eculiari <span dir="ltr" style="left: calc(var(--scale-factor)*195.41px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91293);" role="presentation">del <span dir="ltr" style="left: calc(var(--scale-factor)*212.93px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.861841);" role="presentation">suo <span dir="ltr" style="left: calc(var(--scale-factor)*232.49px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.882591);" role="presentation">mestiere <span dir="ltr" style="left: calc(var(--scale-factor)*275.93px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.910062);" role="presentation">interrogandosi <span dir="ltr" style="left: calc(var(--scale-factor)*348.07px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912907);" role="presentation">sui <span dir="ltr" style="left: calc(var(--scale-factor)*364.99px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.948558);" role="presentation">modi <span dir="ltr" style="left: calc(var(--scale-factor)*392.47px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00214);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*404.71px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.952803);" role="presentation">cui <span dir="ltr" style="left: calc(var(--scale-factor)*422.23px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.23146);" role="presentation">il <span dir="ltr" style="left: calc(var(--scale-factor)*431.71px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.856257);" role="presentation">suo <span dir="ltr" style="left: calc(var(--scale-factor)*451.15px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91579);" role="presentation">lavora <span dir="ltr" style="left: calc(var(--scale-factor)*483.94px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.928113);" role="presentation">influenza <span dir="ltr" style="left: calc(var(--scale-factor)*531.34px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.930193);" role="presentation">la <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.88143);" role="presentation">creazione <span dir="ltr" style="left: calc(var(--scale-factor)*120.86px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9182);" role="presentation">artistica. <span dir="ltr" style="left: calc(var(--scale-factor)*164.90px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.926504);" role="presentation">Attraverso <span dir="ltr" style="left: calc(var(--scale-factor)*218.57px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.980488);" role="presentation">l’analisi <span dir="ltr" style="left: calc(var(--scale-factor)*260.21px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91293);" role="presentation">dei <span dir="ltr" style="left: calc(var(--scale-factor)*277.85px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.865967);" role="presentation">due <span dir="ltr" style="left: calc(var(--scale-factor)*298.13px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.03077);" role="presentation">ultimi <span dir="ltr" style="left: calc(var(--scale-factor)*330.07px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.966448);" role="presentation">lavori, <span dir="ltr" style="left: calc(var(--scale-factor)*364.03px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901975);" role="presentation">Book <span dir="ltr" style="left: calc(var(--scale-factor)*391.63px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925952);" role="presentation">is a <span dir="ltr" style="left: calc(var(--scale-factor)*411.67px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.897147);" role="presentation">Book <span dir="ltr" style="left: calc(var(--scale-factor)*439.15px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925952);" role="presentation">is a <span dir="ltr" style="left: calc(var(--scale-factor)*459.19px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901975);" role="presentation">Book e <span dir="ltr" style="left: calc(var(--scale-factor)*495.10px); top: calc(var(--scale-factor)*343.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.911309);" role="presentation">Macbeth, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.930193);" role="presentation">le <span dir="ltr" style="left: calc(var(--scale-factor)*84.26px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.839621);" role="presentation">cose <span dir="ltr" style="left: calc(var(--scale-factor)*109.22px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.860071);" role="presentation">nascoste, <span dir="ltr" style="left: calc(var(--scale-factor)*157.22px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.924567);" role="presentation">si <span dir="ltr" style="left: calc(var(--scale-factor)*168.86px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.904152);" role="presentation">evince <span dir="ltr" style="left: calc(var(--scale-factor)*203.81px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.939913);" role="presentation">quello <span dir="ltr" style="left: calc(var(--scale-factor)*237.53px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.858738);" role="presentation">che <span dir="ltr" style="left: calc(var(--scale-factor)*257.81px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.887772);" role="presentation">potrebbe <span dir="ltr" style="left: calc(var(--scale-factor)*303.53px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.814107);" role="presentation">essere <span dir="ltr" style="left: calc(var(--scale-factor)*336.43px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.966701);" role="presentation">definito <span dir="ltr" style="left: calc(var(--scale-factor)*377.47px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.884254);" role="presentation">come <span dir="ltr" style="left: calc(var(--scale-factor)*407.11px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.29175);" role="presentation">“lo <span dir="ltr" style="left: calc(var(--scale-factor)*425.47px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.875571);" role="presentation">sguardo <span dir="ltr" style="left: calc(var(--scale-factor)*467.02px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.919675);" role="presentation">del <span dir="ltr" style="left: calc(var(--scale-factor)*485.38px); top: calc(var(--scale-factor)*356.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.931084);" role="presentation">dramaturg” <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.883952);" role="presentation">quale <span dir="ltr" style="left: calc(var(--scale-factor)*101.06px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89259);" role="presentation">connettore <span dir="ltr" style="left: calc(var(--scale-factor)*154.70px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.924024);" role="presentation">delle <span dir="ltr" style="left: calc(var(--scale-factor)*181.22px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.894416);" role="presentation">diverse <span dir="ltr" style="left: calc(var(--scale-factor)*218.93px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.944987);" role="presentation">parti <span dir="ltr" style="left: calc(var(--scale-factor)*244.13px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91293);" role="presentation">del <span dir="ltr" style="left: calc(var(--scale-factor)*261.89px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.936353);" role="presentation">lavoro <span dir="ltr" style="left: calc(var(--scale-factor)*295.61px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91293);" role="presentation">del <span dir="ltr" style="left: calc(var(--scale-factor)*313.37px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.908555);" role="presentation">gruppo. <span dir="ltr" style="left: calc(var(--scale-factor)*353.47px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.196);" role="presentation">Il <span dir="ltr" style="left: calc(var(--scale-factor)*363.79px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.940759);" role="presentation">lavoro è <span dir="ltr" style="left: calc(var(--scale-factor)*406.03px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.871846);" role="presentation">stato <span dir="ltr" style="left: calc(var(--scale-factor)*431.83px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.945392);" role="presentation">fatto <span dir="ltr" style="left: calc(var(--scale-factor)*457.03px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00214);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*469.54px); top: calc(var(--scale-factor)*370.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.910586);" role="presentation">collaborazione <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893485);" role="presentation">con <span dir="ltr" style="left: calc(var(--scale-factor)*92.30px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.903245);" role="presentation">Simona <span dir="ltr" style="left: calc(var(--scale-factor)*132.02px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915577);" role="presentation">Gonella, <span dir="ltr" style="left: calc(var(--scale-factor)*175.94px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.858738);" role="presentation">che <span dir="ltr" style="left: calc(var(--scale-factor)*195.65px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.849175);" role="presentation">ha <span dir="ltr" style="left: calc(var(--scale-factor)*209.93px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.854065);" role="presentation">concesso <span dir="ltr" style="left: calc(var(--scale-factor)*256.25px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.959243);" role="presentation">all’autrice <span dir="ltr" style="left: calc(var(--scale-factor)*307.85px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.976712);" role="presentation">dell’articolo <span dir="ltr" style="left: calc(var(--scale-factor)*369.55px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.974171);" role="presentation">l’intervista e i <span dir="ltr" style="left: calc(var(--scale-factor)*439.27px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938302);" role="presentation">materiali <span dir="ltr" style="left: calc(var(--scale-factor)*484.90px); top: calc(var(--scale-factor)*384.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.977266);" role="presentation">utilizzati. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902758);" role="presentation">The <span dir="ltr" style="left: calc(var(--scale-factor)*94.46px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.934208);" role="presentation">article <span dir="ltr" style="left: calc(var(--scale-factor)*128.18px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.860251);" role="presentation">deals <span dir="ltr" style="left: calc(var(--scale-factor)*156.74px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999813);" role="presentation">with <span dir="ltr" style="left: calc(var(--scale-factor)*181.94px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*200.45px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.908651);" role="presentation">becoming <span dir="ltr" style="left: calc(var(--scale-factor)*251.57px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*265.37px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*283.85px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.936986);" role="presentation">polyvalent <span dir="ltr" style="left: calc(var(--scale-factor)*338.35px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*359.47px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.894602);" role="presentation">sophisticated <span dir="ltr" style="left: calc(var(--scale-factor)*425.95px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.958081);" role="presentation">figure <span dir="ltr" style="left: calc(var(--scale-factor)*458.47px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*472.30px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*490.78px); top: calc(var(--scale-factor)*419.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901975);" role="presentation">dramaturg <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00091);" role="presentation">within <span dir="ltr" style="left: calc(var(--scale-factor)*107.54px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.952952);" role="presentation">Italian <span dir="ltr" style="left: calc(var(--scale-factor)*142.82px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.872523);" role="presentation">theatre <span dir="ltr" style="left: calc(var(--scale-factor)*180.14px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901985);" role="presentation">practice. <span dir="ltr" style="left: calc(var(--scale-factor)*226.01px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.984);" role="presentation">In <span dir="ltr" style="left: calc(var(--scale-factor)*240.65px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941819);" role="presentation">particular, <span dir="ltr" style="left: calc(var(--scale-factor)*294.41px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.947119);" role="presentation">by <span dir="ltr" style="left: calc(var(--scale-factor)*311.21px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925288);" role="presentation">examining <span dir="ltr" style="left: calc(var(--scale-factor)*366.67px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*386.11px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.895171);" role="presentation">example <span dir="ltr" style="left: calc(var(--scale-factor)*431.47px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*446.23px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.903245);" role="presentation">Simona <span dir="ltr" style="left: calc(var(--scale-factor)*487.78px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915577);" role="presentation">Gonella, <span dir="ltr" style="left: calc(var(--scale-factor)*533.50px); top: calc(var(--scale-factor)*432.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.116);" role="presentation">it <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.883565);" role="presentation">attempts <span dir="ltr" style="left: calc(var(--scale-factor)*117.38px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.936);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*131.42px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.94133);" role="presentation">outline <span dir="ltr" style="left: calc(var(--scale-factor)*169.34px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*188.66px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.914422);" role="presentation">peculiar <span dir="ltr" style="left: calc(var(--scale-factor)*231.77px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.922154);" role="presentation">traits <span dir="ltr" style="left: calc(var(--scale-factor)*260.45px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*275.09px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.880969);" role="presentation">her <span dir="ltr" style="left: calc(var(--scale-factor)*295.01px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941277);" role="presentation">craft <span dir="ltr" style="left: calc(var(--scale-factor)*321.77px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.947119);" role="presentation">by <span dir="ltr" style="left: calc(var(--scale-factor)*338.47px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912712);" role="presentation">questioning <span dir="ltr" style="left: calc(var(--scale-factor)*399.07px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*418.39px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.899342);" role="presentation">ways <span dir="ltr" style="left: calc(var(--scale-factor)*447.67px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00214);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*461.74px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.954368);" role="presentation">which <span dir="ltr" style="left: calc(var(--scale-factor)*495.70px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.849175);" role="presentation">her <span dir="ltr" style="left: calc(var(--scale-factor)*515.62px); top: calc(var(--scale-factor)*446.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.970797);" role="presentation">work <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.910552);" role="presentation">influences <span dir="ltr" style="left: calc(var(--scale-factor)*124.34px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.944909);" role="presentation">artistic <span dir="ltr" style="left: calc(var(--scale-factor)*160.22px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.904499);" role="presentation">creation. <span dir="ltr" style="left: calc(var(--scale-factor)*205.01px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.923903);" role="presentation">Through <span dir="ltr" style="left: calc(var(--scale-factor)*249.41px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*267.17px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893287);" role="presentation">analysis <span dir="ltr" style="left: calc(var(--scale-factor)*309.05px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*322.13px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.880969);" role="presentation">her <span dir="ltr" style="left: calc(var(--scale-factor)*340.51px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.964114);" role="presentation">two <span dir="ltr" style="left: calc(var(--scale-factor)*361.63px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.897692);" role="presentation">most <span dir="ltr" style="left: calc(var(--scale-factor)*388.15px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.877145);" role="presentation">recent <span dir="ltr" style="left: calc(var(--scale-factor)*420.67px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.934872);" role="presentation">works, <span dir="ltr" style="left: calc(var(--scale-factor)*456.19px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901975);" role="presentation">Book <span dir="ltr" style="left: calc(var(--scale-factor)*483.94px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925952);" role="presentation">is a <span dir="ltr" style="left: calc(var(--scale-factor)*504.22px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901975);" role="presentation">Book <span dir="ltr" style="left: calc(var(--scale-factor)*531.94px); top: calc(var(--scale-factor)*460.53px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925952);" role="presentation">is a <span dir="ltr" style="left: calc(var(--scale-factor)*83.66px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901975);" role="presentation">Book <span dir="ltr" style="left: calc(var(--scale-factor)*113.90px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*136.94px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.911309);" role="presentation">Macbeth, <span dir="ltr" style="left: calc(var(--scale-factor)*187.58px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.930193);" role="presentation">le <span dir="ltr" style="left: calc(var(--scale-factor)*201.89px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.839621);" role="presentation">cose <span dir="ltr" style="left: calc(var(--scale-factor)*228.77px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.86232);" role="presentation">nascoste, <span dir="ltr" style="left: calc(var(--scale-factor)*278.81px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.918383);" role="presentation">we <span dir="ltr" style="left: calc(var(--scale-factor)*298.49px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.914815);" role="presentation">gain <span dir="ltr" style="left: calc(var(--scale-factor)*324.89px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.943599);" role="presentation">insight <span dir="ltr" style="left: calc(var(--scale-factor)*363.31px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.967322);" role="presentation">into <span dir="ltr" style="left: calc(var(--scale-factor)*387.67px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917758);" role="presentation">what <span dir="ltr" style="left: calc(var(--scale-factor)*416.59px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.928034);" role="presentation">could <span dir="ltr" style="left: calc(var(--scale-factor)*448.87px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.849175);" role="presentation">be <span dir="ltr" style="left: calc(var(--scale-factor)*465.82px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.911817);" role="presentation">defined <span dir="ltr" style="left: calc(var(--scale-factor)*507.46px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.785162);" role="presentation">as <span dir="ltr" style="left: calc(var(--scale-factor)*523.06px); top: calc(var(--scale-factor)*474.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.894304);" role="presentation">'the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.889757);" role="presentation">dramaturg's <span dir="ltr" style="left: calc(var(--scale-factor)*131.18px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.855689);" role="presentation">gaze' <span dir="ltr" style="left: calc(var(--scale-factor)*158.54px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.785162);" role="presentation">as a <span dir="ltr" style="left: calc(var(--scale-factor)*180.26px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.897494);" role="presentation">connector <span dir="ltr" style="left: calc(var(--scale-factor)*230.69px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.0116);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*243.89px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*261.77px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.956272);" role="presentation">different <span dir="ltr" style="left: calc(var(--scale-factor)*306.29px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.87694);" role="presentation">parts <span dir="ltr" style="left: calc(var(--scale-factor)*332.83px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*346.03px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.936);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*363.79px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.895458);" role="presentation">group's <span dir="ltr" style="left: calc(var(--scale-factor)*401.83px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.967701);" role="presentation">work. <span dir="ltr" style="left: calc(var(--scale-factor)*432.79px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902758);" role="presentation">The <span dir="ltr" style="left: calc(var(--scale-factor)*454.51px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.970797);" role="presentation">work <span dir="ltr" style="left: calc(var(--scale-factor)*482.38px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.876101);" role="presentation">was <span dir="ltr" style="left: calc(var(--scale-factor)*504.22px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.874363);" role="presentation">done <span dir="ltr" style="left: calc(var(--scale-factor)*530.74px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00214);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.929237);" role="presentation">collaboration <span dir="ltr" style="left: calc(var(--scale-factor)*139.34px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999813);" role="presentation">with <span dir="ltr" style="left: calc(var(--scale-factor)*164.78px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.903245);" role="presentation">Simona <span dir="ltr" style="left: calc(var(--scale-factor)*205.61px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915577);" role="presentation">Gonella, <span dir="ltr" style="left: calc(var(--scale-factor)*250.61px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938846);" role="presentation">who <span dir="ltr" style="left: calc(var(--scale-factor)*275.33px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.885251);" role="presentation">granted <span dir="ltr" style="left: calc(var(--scale-factor)*315.53px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*334.27px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.900088);" role="presentation">author <span dir="ltr" style="left: calc(var(--scale-factor)*368.95px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*382.99px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*401.83px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.934208);" role="presentation">article <span dir="ltr" style="left: calc(var(--scale-factor)*435.91px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*454.63px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.955692);" role="presentation">interview <span dir="ltr" style="left: calc(var(--scale-factor)*503.98px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*525.34px); top: calc(var(--scale-factor)*501.93px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*515.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901479);" role="presentation">materials <span dir="ltr" style="left: calc(var(--scale-factor)*118.94px); top: calc(var(--scale-factor)*515.73px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.850716);" role="presentation">used.